Upon the threshold between what is gone and what is yet to come: |the concept of time in A. H. Tanpınar's novels - Köroğlu, Erol. (Thesis (M.A.) - Bogazici University. Institute of Social Sciences, 1996., 1996)
Ahmet Hamdi Tanpmar considers time as a continuity which, he thinks, proceeds along the line of past-present-future; and he uses this temporal conceptualization as one of the main themes of his poems, fictions and non-fictions. The continuity of time which is experienced on individual and social levels is broken during the Westernization process which starts with the Tanzimat period. Believing that the dilemma of belonging to the East or West could be overcome by taking refuge in the natural wholeness of culture, Tanpmar narrates the search of the divided self for wholeness in his novels. In this study, first the development of the concept of time in the history of mankind is discussed in order to clarify the concept of time in Tanpmar's novels. What follows is the analysis of Tanpmar's understanding of time with reference to the problem of Westernization and the thoughts of authors like Yahya Kemal and Abdülhak Sinasi Hisar. In the last section, Tanpmar's five novels are studied one by one with respect to terms like time, continuity, wholeness and dividedness. In the conclusion, it is claimed that Tanpmar's novels formally exhibit the wholeness his heroes fail to reach.
Keywords: Time in literature.